The Covid-19 pandemic: towards a societally engaged IB perspective. Issue 2 (6th May 2021) - Dörrenbächer, Christoph; Sinkovics, Rudolf R.; Becker-Ritterspach, Florian; Boussebaa, Mehdi; Curran, Louise; de Jonge, Alice; Khan, Zaheer
Abstract : Purpose: This viewpoint takes up the Covid-19 pandemic as a trigger for a research agenda around societally engaged international business (IB) research. Design/methodology/approach: The paper is organized as a viewpoint. First, it provides an overview of Covid-19 research in business and management and IB in particular. Second, it introduces a societally engaged IB perspective, around poverty and human rights as well as trade. Findings: The paper offers an annotated introduction to the paper contributions of the special issue with three clusters, "re-reading the crisis", "crisis protectionism" and "firm strategies during the pandemic". Research limitations/implications: The paper points to future research opportunities in terms of crisis management and societally engaged IB research. Practical implications: The Covid-19 crisis poses new questions for research on international business and its related disciplines. In particular, the political, economic and societal disruption which the pandemic has caused highlights the importance of addressing broader societal issues such as climate change, poverty and inequality through a purposeful and forward-looking research agenda. Originality/value: The paper and the special issue are some of the first combined research outputs on the Covid-19 pandemic in international business.